2018
DOI: 10.1177/0170840618759817
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the Transparency-Secrecy Nexus: Frontstage and backstage behaviour in a political party

Abstract: While the majority of research promotes the idea of transparency and puts all efforts into refining existing concepts, critical studies emphasize the performativity of measures to increase visibility. The article theorizes the nexus of transparency and secrecy by drawing on Erving Goffman’s frontstage/backstage theory, according to which actors vie to maintain boundaries of visibility by alternating these two types of situations. Using this approach, the article interprets the emergence of new forms of secrecy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 38 publications
2
88
0
2
Order By: Relevance
“…Paying special attention to network agency, we trace how Apprenticeship Network strategically front and back‐staged (see Goffman, ) agreed‐upon rules and norms in order to facilitate the formation, maintenance and deletion of the new tie to EnergyCorp. By this we mean, in line with previous management and organization research using this Goffmanian approach (Mair and Hehenberger, ; Manning, ; Ringel, ), that the other partner firms emphasized and directly referred to existing rules at the network level at certain times, while ignoring and downplaying the relevance of the same rules at other times. Engaging in these coordinative practices, Apprenticeship Network managed the partnership in light of significant conflicts and tensions related to the size differentials, albeit at the cost of EnergyCorp's network exit.…”
Section: Introductionmentioning
confidence: 77%
“…Paying special attention to network agency, we trace how Apprenticeship Network strategically front and back‐staged (see Goffman, ) agreed‐upon rules and norms in order to facilitate the formation, maintenance and deletion of the new tie to EnergyCorp. By this we mean, in line with previous management and organization research using this Goffmanian approach (Mair and Hehenberger, ; Manning, ; Ringel, ), that the other partner firms emphasized and directly referred to existing rules at the network level at certain times, while ignoring and downplaying the relevance of the same rules at other times. Engaging in these coordinative practices, Apprenticeship Network managed the partnership in light of significant conflicts and tensions related to the size differentials, albeit at the cost of EnergyCorp's network exit.…”
Section: Introductionmentioning
confidence: 77%
“…In addition to the more well-known scenario where frontstage compliance acts as a mask for backstage resistance, recent studies have also shown that frontstage resistance can be coupled with backstage compliance (Ybema and Horvers, 2017). The 'darker side' of the backstage/frontstage relationship has also been revealed by research that has shown how the backstage is used to conceal misconduct (Laguecir and Leca, 2019) and keep secrets from being exposed (Ringel, 2019). Studies have also shown how backstage activity is strategically concealed in the myths and fabrications presented on the frontstage, for example, in environmental reporting and CSR reporting (Bansal and Kistruck, 2006;Solomon et al, 2013), management accounting (Goretzki and Messner, 2019) and auditing (Parker et al, 2019;Pentland and Carlile, 1996;Roussy and Rodrigue, 2018).…”
Section: A Dramaturgical Perspective On Changing Strategy Arrangementsmentioning
confidence: 99%
“…Samme tendens kan jeg bekraefte inden for mit eget felt, organisationsstudier, hvor en gruppe af saerligt yngre forskere har givet sig i kast med at formulere en eksplicit organisatorisk tilgang til studiet af politiske partier (f.eks. Moufahim et al 2015;Husted 2018;Ringel 2019). Som jeg selv og andre har argumenteret for, kan denne tilgang beskrives som 'immersiv', da den netop retter sig mod en dybdegående og kvalitativ forståelse af partiernes interne dynamikker (Husted 2019).…”
Section: Partilitteraturen I Perspektivunclassified